Vermeer, faith in painting - Arasse, Daniel 1944-2003 (Princeton University Press, 1994)
By examining Vermeer's approach to image-making, the author finds that his works demonstrate the concept of painting as a medium through which the viewer senses the ungraspable and mysterious presence of life. Not only does this concept of painting carry on the traditions of Classical Antiquity and the High Renaissance, but it also relates to Catholic ideas about spiritual meditation and the power of images
Includes bibliographical references (p. 127-132) and index
Keywords: Vermeer van Delft, Jan; Vermeer, Johannes <1632-1675> - Critique et interprétation; Vermeer, Johannes <1632-1675> -- Criticism and interpretation; Vermeer van Delft, Jan -- 1632-1675; Netherlands; Paintings; Spiritualiteit; Spiritualité dans l'art; Spirituality in art; Malerei; Niederlande